Comparison of the Effectiveness of 532 nm and 660 nm Diode Laser on MRSA Viability in Different Tissue Thicknesses in Vitro - A. Turki Aldalawi, Ali (Al-Nahrain Journal of Science, 2024)
Laser-mediated therapeutic approaches have offered multiple advantages in reducing cutaneous microbial complications across different environments along with biological processes. However, the application of such an approach in clinical trials of different tissues has been very difficult and cannot be applied to improve microbial control investigations across different tissue sites. This study aims to provide a comparative perspective to evaluate the analgesic parameters of 530nm and 660nm lasers at MRSA-infected tissue sites under laboratory conditions. To investigate this, the light penetration depths and transport properties will be initially investigated, providing insight into this strategy and its optimization in laser-based microbial decontamination efficiency. This type of treatment facilitates the development of new and untested protocols that take into account the optical properties of MRSA-infected tissues in different clinical settings, to ensure optimal control of microbial pathogens while minimizing the potential for future infection of surrounding tissues. Wavelengths of 660 nm provided acceptable efficiency for controlling pathogens in different 3 mm thick cattle meat samples, confirming the effectiveness of this technique. In contrast, the 530nm wavelengths provided better efficacy in beef tissue samples of 5mm and 10mm thickness, demonstrating the validity of the advantages of laser therapy for diverse tissues compared to standard antibiotics, while indexing new treatment protocols against pathogens in various therapeutic settings. This treatment approach offers several advantages of laser properties over conventional therapies while reducing the concerns expected with laser-based interventions. Thus, this technique can be calibrated in the laboratory to ensure light transmittance considerations are matched to target site characteristics to reduce microbial risk and ensure patient safety through optimal tissue conditions.